Perjanjian Perkawinan Baru: Model Perjanjian Perkawinan Berbasis Maqashid Syariah Sebagai Solusi Menguatkan Ketahanan Keluarga - Rasidin, Mhd.; Sidqi, Imaro; Witro, Doli; Busni, Darti (Al-Ulum, 2023)
This article aims to discuss marriage agreements in strengthening family resilience in Indonesia and tries to implement them with a different concept than the previous concept through the basis of Maqashid Syariah as its construction epistemology. This article is a juridical-normative research, which uses the maqashid sharia approach and gender through descriptive-qualitative analysis. This article finds that marriage agreements in Indonesia are described or based on several existing laws, including; the Civil Code, Marriage Law (UUP), and Compilation of Islamic Law (KHI). The marriage agreement must be implemented because the marriage agreement itself is considered very important to be formed by each family because it can lead the family to become sakinah, mawadah, and waramah. In addition, marriage agreements, both formal and substantial, need to be revised in detail and not discriminate so that they have a new concept that is more up-to-date and represents legal objectives so that it can strengthen the resilience of families in Indonesia, the impact of which is to reduce the ever-increasing divorce.